PENGUKURAN TOTAL HARMONIC DISTORTION (THD) TERHADAP LAMPU HEMAT ENERGI (LHE) DAN LIGHT-EMITTING DIODE (LED) - Fernando Jeremia Siahaan; Eva Magdalena Silalahi; Bambang Widodo; Robinson Purba (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2020)
Abstract. Along with the rapid development of power electronics technology which is also useful for saving electrical energy. This technology is also used in lighting such as energy saving lamps (LHE) and light-emitting diode (LED). However, LHE and LED are non-linear loads that cause electrical power quality problems, namely producing voltage and current waveforms that are no longer sinusoidal or distorted waveforms. Distorted waves cause harmonic waves which have a frequency multiple of the fundamental frequency. The sum of the effective values of the harmonic components of the distorted waveform is calculated in terms of total harmonic distortion (THD). This study found that the THD value of the voltage generated by the LHE and LED loads was equal is 0.80% -1.3%, while the current THD generated by the LHE load was 68.57% - 78.68% and the LED was 72, 15% - 86.04%. The current THD value generated by the LHE and LED loads does not fulfil the IEEE Std 519-2014 harmornic distortion limits. The use of LHE and LED lamps simultaneously will reduce the resulting current THD value by 3% to 9%.